Finite Element Explicit Dynamics Simulation of an Impact Cutting Mechanism Analysis of Populus tomentosa Branches - Shihong Ba; Yichen Ban; Kun Lyu; Yang Liu; Jian Wen; Wenbin Li (BioResources, 2024)
The branch impact failure mechanism has gradually received attention from scholars, along with the application of impact cutting methods in plantation forest pruning. In this paper, the impact cutting failure mechanism of Populus tomentosa branches was mainly studied. The impact cutting process of branches was simulated by using Finite Element Method (FEM)-based explicit dynamics. The stress change and deformation characteristics in the branch failure process were studied. A theoretical model of branch impact cutting mechanism with branch diameter, cutting clearance, and branch angle as the main factors was proposed. The model describes the branch cutting damage process and the changing characteristics of cutting force. A branch failure state equation was proposed to describe the branch impact cutting failure patterns. The forest experiment was conducted to validate the branch impact cutting mechanism and the branch failure state equation. This work fills a vacancy of relevant theory and provides a theoretical basis for the future development of forestry and agricultural equipment using impact cutting.